PENGEMBANGAN BAHAN AJAR MATA PELAJARAN BAHASA INDONESIA BERBASIS CERITA RAKYAT KABUPATEN BANJARNEGARA - nia ulfa martha; novita pri andini (JINoP (Jurnal Inovasi Pembelajaran), 2019)
This research is based on the fact that teaching materials are not yet available as a best friend for teachers in delivering Indonesian language learning at the SMA / MA class X semester 1 of KD 3.7 and 4.7. The purpose of this study was to produce teaching materials for Indonesian language for class X semesters 1 KD 3.7 and 4.7 based on Banjarnegara Regency folklore. This research is a development research with a qualitative descriptive analysis technique. According to experts teaching material has a percentage of validity level 88.5% with a valid category, according to media experts teaching material has a percentage of validity level 80% with a valid category, according to learning experts namely Indonesian language subject teachers have a percentage of validity level 83.7 % with valid categories. Based on the results of research according to class X students of SMA Muhammadiyah Banjarnegara as users, this teaching material greatly facilitates students in understanding folklore. This can be seen from the result of filling out the questionnaire about response student of class X to the teaching materials of the developmet result which have a percentage of validity 91.5%. Suggestions include for product utilization, product dissemination, and further development needs.